The effect of sports, health, positive citizenship, life skills and extracurricular activities on eliminating university violence among Jordanian university students - Aljbour, Nayef Mufadi (Journal of Educational and Psychological Sciences, 2021)
Extracurricular activities, sports, health and positive citizenship courses constitute a major and important factor in refining and changing students ’personality in various aspects, in which the student participates and which contributes to developing his skills and abilities and helping him to face the problems he faces. The study aimed to know the effect of this course and activities in eliminating the phenomenon Violence in Jordanian universities. The researcher used the descriptive approach for its suitability and the nature of the study. He used the questionnaire as a study tool. And designed by the researcher after conducting good testing standards (honesty, objectivity, consistency), which are an important aspect of university education, as the activities work to remove the barriers of traditional bonding between the teacher and students in the classroom, where they play a major role in the formation and growth of personality in various mental aspects. The psychological and social aspects of student life through the different situations in which the student participates in these activities, which develops his skills and abilities and helps him to resist his problems. The study showed that there were no statistically significant differences at the level of significance (α≤0.05) in the role of sports, health, positive citizenship and life skills courses in reducing the phenomenon of university violence as a whole according to the variables (gender, area of ​​residence, age, academic year)), While the study found statistically significant differences at the level of significance (α≤0.05) in the role of sports, health, positive citizenship and life skills courses in reducing the phenomenon of university violence as a whole according to the variable of specialization. In light of the results of the study, the researcher concluded a number of recommendations.
Keywords: sports and health; positive citizenship; extracurricular activities; the phenomenon of university violence